Using discourse analysis to improve classroom interaction [ - Rex, Lesley A.; Schiller, Laura , 1949- (Routledge, 2009)
"This accessible "how-to" text is about classroom interaction - how to study it and how to use that knowledge to improve teaching and learning. Actually showing what critical, constructionist, sociocultural perspectives on teaching, learning, and schooling are and what they can do, it makes discourse analysis understandable and useful to teachers and other nonlinguists."--BOOK JACKET.